Analysis of the Implementation of Science Teaching Materials Based on Ecotourism Education at SMPN East Lombok Regency - Yayuk Andayani; Abdul Syukur; Agus Ramdani; Muhammad Yustiqvar; Muntari; Nurhidayat Martin; Nanda Aulia Pratiwi (Lembaga Bale Literasi, 2026)
Edu-ecotourism in the context of science learning is an educational approach that integrates the concept of ecotourism into the learning process, which offers an effective way to teach science material contextually, experience-based, and relevant to everyday life and can instill an attitude of caring for the environment around students, so that learning becomes more enjoyable and meaningful. However, the fact in the field is that there are still many schools that have not been able to implement edu-ecotourism-based science learning due to various obstacles including the availability of edu-ecotourism-based teaching materials and the lack of teacher knowledge about edu-ecotourism. From previous research, researchers have developed ecotourism/ethnoscience-based science teaching materials that connect community knowledge of the cultural products of the Sasak, Samawa and Mbojo tribes with chemistry or science materials, but have not been widely implemented in schools. Based on the role of edu-ecotourism in the context of science learning in schools is very important, the implementation of ecotourism-based science teaching materials is necessary. Therefore, the purpose of this study is to analyze the implementation of ecotourism-based science teaching materials at SMPN East Lombok Regency. This study uses a qualitative descriptive approach to describe the existing phenomena in depth regarding the implementation of ecotourism-based science teaching materials at SMPN East Lombok Regency, including the obstacles faced by teachers and students, as well as the learning experiences of students obtained after the learning. The research instrument was the research team with the help of questionnaires, observation sheets and interview guidelines. Quantitative data were analyzed using descriptive statistics and qualitative data were analyzed using an interactive model. The implementation of ecotourism-based science teaching materials went very well and was received positively by the majority of teachers. A total of 45 teachers actively tried to use at least two of the five teaching materials socialized in their classroom learning. The results of in-depth interviews with 15 teachers stated that the teaching materials used helped them bridge the gap between the theory in textbooks and the reality that exists in the students' environment. Teachers felt that abstract science concepts became easier for students to understand when they saw their direct application in their culture and local wisdom.